A comprehensive experimental study on the performance of pumice powder in self-compacting concrete (SCC). Issue 6 (2nd November 2018) - Askarian, Mahya; Fakhretaha Aval, Siavash; Joshaghani, Alireza
Abstract : This study presents results on the performance of self-compacting concrete (SCC) mixtures containing pumice powder as a pozzolan in various proportions. The required superplasticizer dosage, used to obtain the desired initial slump flow, was determined when compared to mixtures containing fly ash or slag. The incorporation of cheap natural pozzolans as an alternative to cementitious materials can improve the fresh properties and durability of concrete. However, the reactivity of natural pozzolans, such as pumice, specifically in the early ages, is always a concern when using thesesupplementary materials . To identify the effects of pumice powder on workability retention of SCC mixtures, the slumps were measured with regards to time elapsed. The effects of pumice, fly ash, and slag on the self-consolidating properties such as slump flow, V-funnel flow, U-box, and J-ring flow, as well as compressive strength, electrical resistivity, and water absorption were investigated. The ordinary Portland cement was partially replaced between 10 and 50% by pumice, fly ash or slag, and the optimum cement replacement dosage for each supplementary cementitious materials (SCMs) is proposed based on a significance factor in different tests. The test results indicated that SCC mixtures containing pumice powder offer greater performance compared to other SCMs.